Composite sodium iron sulfate positive electrode material and preparation method thereof, positive electrode and sodium ion battery

By embedding the three-dimensional conductive network and cladding formed by PEDOT in the sodium ferrosulfate positive electrode material, the problem of oxidation and decomposition of the material and poor conductivity at high voltage is solved, and the electrochemical performance and stability of the material are improved.

CN116779808BActive Publication Date: 2025-02-07JIANGSU PYLON BATTERY CO LTD

Patent Information

Application Number
CN202310755581.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-25
Publication Date
2025-02-07
Estimated Expiration
2043-06-25

AI Technical Summary

Technical Problem

Iron-based sulfate positive electrode materials are easily oxidized and decomposed at high voltages, and poor conductivity leads to low sodium storage capacity and poor rate performance. At the same time, the material is easy to absorb water and oxidize, resulting in material failure.

Method used

The three-dimensional conductive network formed by PEDOT is embedded in the sodium ferrous sulfate matrix and forms a conductive cladding layer on the surface. The water solubility of PEDOT is improved by introducing PSS, so that it is fully dispersed with sodium sulfate and ferrous sulfate to form a composite sodium ferrous sulfate positive electrode Material.

Benefits of technology

The conductivity, capacity and magnification of the sodium ferric sulfate positive electrode material is improved, the interface stability of the material is enhanced, the oxidation and decomposition at high voltage is avoided, and the cost and environmental hazards of the material are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116779808B_ABST
    Figure CN116779808B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium electric materials, and discloses a composite sodium iron sulfate positive electrode material and a preparation method thereof, a positive electrode and a sodium ion battery. The composite sodium iron sulfate positive electrode material, the particles of the positive electrode material include a sodium iron sulfate matrix, a three-dimensional conductive network embedded in the sodium iron sulfate matrix, and a conductive coating layer coated outside the sodium iron sulfate matrix; the three-dimensional conductive network and the conductive coating layer are both formed by PEDOT. The preparation method comprises mixing PSS, EDOT, sodium sulfate, ferrous sulfate and an oxidant as an initiator in an aqueous solution to fully react to obtain a precursor solution; drying the precursor solution, and then heat treating to obtain a composite sodium iron sulfate positive electrode material. The positive electrode is prepared using the above-mentioned positive electrode material. The sodium ion battery comprises the above-mentioned positive electrode. The positive electrode material has good conductivity, capacity, rate and interface stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium electric materials, and in particular to a composite sodium iron sulfate positive electrode material and a preparation method thereof, a positive electrode and a sodium ion battery. Background Art

[0002] At present, the cathode materials of sodium ion batteries are mainly divided into three categories: layered oxides, polyanions and Prussian white derivatives. Among them, polyanion materials have attracted much attention because polyanion polyhedra and transition metal ion polyhedra are connected by strong covalent bonds to form a three-dimensional network structure, which has excellent structural stability and long cycle potential.

[0003] Iron-based polyanion cathode materials have developed rapidly due to their rich iron 3 content and environmental friendliness. Among them, the working potential of iron-based pyrophosphate cathode materials is low (~3.0V vs.Na+ / Na) and the energy density is low. Iron-based sulfate materials have a higher working potential (~3.7V vs.Na+ / Na) and can bring higher energy density, so they have attracted attention.

[0004] However, this type of material has a high operating voltage, and the upper limit of the charging voltage exceeds 4.2V vs. Na+ / Na, which can easily cause oxidative decomposition of the electrolyte at the positive electrode. In addition, this type of iron-based sulfate usually has poor conductivity, resulting in low sodium storage capacity and poor rate performance. At the same time, when this type of material comes into contact with air, it is also easy to absorb water and oxidize, causing the material to fail. The usual solution is to improve the conductivity and hydrophobicity of iron-based sulfates by composite carbon-based materials.

[0005] However, due to the high working potential of iron-based sulfate, the upper limit of the charging voltage is usually higher than 4.2V vs. Na + / Na, the electrolyte is easily oxidized and decomposed on the surface of iron-based sulfate at this voltage. The method of doping or coating iron-based sodium sulfate with carbon-based materials alone cannot effectively inhibit the oxidative decomposition of the electrolyte under high voltage. In addition, since iron-based sulfate will decompose at temperatures exceeding 500°C, it cannot be treated by conventional high-temperature carbon coating methods. Therefore, carbon nanotubes are usually used for compounding, and the amount of carbon nanotubes used is relatively large, and the cost is relatively high.

[0006] Therefore, it is of great significance for sodium iron sulfate materials to develop materials that simultaneously improve the oxidation stability under high voltage and the electrical conductivity of the material itself.

[0007] Among them, conductive polymer materials have good conductivity in themselves, and as polymer materials, they also have good chemical stability. Therefore, they are often used as coating materials for battery materials to improve the conductivity and interface stability of the materials. However, when conductive polymers are usually used for coating, it is necessary to prepare the battery materials first, then dissolve the polymer monomers in an organic solvent, mix them with the battery materials, and then polymerize them. Conductive polymers can often only be coated on the surface of the material and cannot form a cross-linked three-dimensional conductive network in the bulk phase. In addition, the synthesis steps are complicated and require the use of organic solvents, which are harmful to the environment and health. Therefore, it is necessary to develop a suitable method to further improve the conductivity while simplifying the process steps and reducing environmental and health hazards.

[0008] In view of this, the present invention is proposed. Summary of the invention

[0009] The object of the present invention is to provide a composite sodium iron sulfate positive electrode material and a preparation method thereof, a positive electrode and a sodium ion battery.

[0010] The present invention is achieved in that:

[0011] In a first aspect, the present invention provides a composite sodium ferric sulfate positive electrode material, wherein the particles of the positive electrode material include a sodium ferric sulfate matrix, a three-dimensional conductive network embedded in the sodium ferric sulfate matrix, and a conductive coating layer coated outside the sodium ferric sulfate matrix; the three-dimensional conductive network and the conductive coating layer are both formed by PEDOT.

[0012] In an optional embodiment, the mass ratio of the sodium ferric sulfate matrix to the PEDOT is 100:1-10.

[0013] In a second aspect, the present invention provides a method for preparing a composite sodium iron sulfate positive electrode material, comprising:

[0014] PSS, EDOT, sodium sulfate, ferrous sulfate and an oxidant as an initiator are mixed and reacted in an aqueous solution to obtain a precursor solution;

[0015] The precursor solution is dried to obtain a PEDOT-PSS composite sodium iron sulfate precursor;

[0016] The sodium iron sulfate precursor is heat-treated at 300-450° C. for 6-24 hours under an inert atmosphere to obtain a composite sodium iron sulfate positive electrode material.

[0017] In an optional embodiment, the method of mixing PSS, EDOT, sodium sulfate, ferrous sulfate and an oxidant as an initiator to react comprises:

[0018] First, add PSS, deionized water and EDOT into the reaction container and stir thoroughly to disperse them evenly;

[0019] Then, sodium sulfate, ferrous sulfate and an oxidant are added to the reaction solution, and the reaction is carried out under constant stirring.

[0020] In an optional embodiment, the oxidant includes at least one of ferric sulfate, sodium persulfate, ammonium persulfate, hydrogen peroxide, and oxygen;

[0021] Preferably, the oxidizing agents are ferric sulfate and sodium persulfate.

[0022] In an optional embodiment, the molar ratio of sodium sulfate to ferrous sulfate is 1:1.5 to 2.5;

[0023] Optionally, the feed mass ratio of PSS to EDOT is 10:1-5.

[0024] In an optional embodiment, the feeding amount is calculated by weight: the total amount of PSS and EDOT is 31-314 parts, the sodium sulfate is 1000 parts, and the ferrous sulfate is 1605-2675 parts;

[0025] Optionally, the oxidant is 1 to 200 parts;

[0026] Optionally, the deionized water is 2500 to 100000 parts.

[0027] In an alternative embodiment, the drying method is spray drying.

[0028] In a third aspect, the present invention provides a positive electrode, which is made using the positive electrode material of the aforementioned embodiment, or the positive electrode material prepared by the preparation method of any one of the aforementioned embodiments.

[0029] In a fourth aspect, the present invention provides a sodium ion battery comprising a positive electrode as described in the aforementioned embodiment.

[0030] The present invention has the following beneficial effects:

[0031] In the composite sodium ferric sulfate positive electrode material provided by the present invention, the conductive network formed by PEDOT is embedded in the sodium ferric sulfate matrix and coated on the surface of the sodium ferric sulfate matrix, which can improve the conductivity, capacity and rate of the sodium ferric sulfate positive electrode material; and because PEDOT has good chemical stability, a coating layer is formed on the surface of the sodium ferric sulfate, which can improve the interface stability of the sodium ferric sulfate positive electrode material.

[0032] In the preparation method provided in an embodiment of the present invention, PSS (sodium polystyrene sulfonate) is introduced during the preparation process, and the solubility of PEDOT in water is improved through the ionic bond interaction between PEDOT and PEDOT, so that PEDOT can form a uniformly dispersed aqueous solution with sodium sulfate and ferrous sulfate, thereby forming a PEDOT-based three-dimensional conductive network structure inside the particles of the composite sodium ferric sulfate positive electrode material finally obtained after heat treatment, rather than just coating PEDOT on the surface of the sodium ferric sulfate particles; and during the heat treatment process, the sulfonic acid group of PSS will decompose, causing the ionic bond between PEDOT-PSS to disappear, which will further improve the conductivity of the final polymer. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0034] Figure 1 It is a sodium iron sulfate material doped and coated with a PEDOT-based conductive polymer;

[0035] Figure 2 It is ordinary sodium iron sulfate material without any doping or coating. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0037] The composite sodium iron sulfate positive electrode material and its preparation method as well as the positive electrode and sodium ion battery provided in the embodiments of the present invention are specifically described below.

[0038] The composite sodium ferric sulfate positive electrode material provided in an embodiment of the present invention comprises particles of a sodium ferric sulfate matrix, a three-dimensional conductive network embedded in the sodium ferric sulfate matrix, and a conductive coating layer coated outside the sodium ferric sulfate matrix; the three-dimensional conductive network and the conductive coating layer are both formed by PEDOT.

[0039] PEDOT is a polymer of EDOT (3,4-ethylenedioxythiophene monomer) with excellent conductive properties. The conductive network formed by PEDOT is embedded in the sodium ferric sulfate matrix and coated on the surface of the sodium ferric sulfate matrix, which can improve the conductivity, capacity and rate of the sodium ferric sulfate positive electrode material; and because PEDOT has excellent chemical stability, a coating layer is formed on the surface of the sodium ferric sulfate, which can improve the interface stability of the sodium ferric sulfate positive electrode material.

[0040] Preferably, in order to ensure that the composite sodium iron sulfate positive electrode material has better electrochemical performance, the mass ratio of the sodium iron sulfate matrix to the PEDOT is 100:1 to 10 (for example, 100:1, 100:2, 100:3, 100:4, 100:5, 100:6, 100:7, 100:8, 100:9 or 100:10); a further preferred range may be, for example, 100:1 to 8, 100:1 to 7, 100:1 to 8. 0:1~6, 100:1~5, 100:1~4, 100:1~3, 100:1~2, 100:2~10, 100:3~10, 100:4~10, 100:5~10, 100:6~10, 100:7~10, 100:8~10, 100:3~7, 100:3~6, 100:3~5, 100:3~4, 100:4~6 or 100:4~5.

[0041] The present invention provides a method for preparing a composite sodium iron sulfate positive electrode material, comprising:

[0042] PSS, EDOT, sodium sulfate, ferrous sulfate and an oxidant as an initiator are mixed and reacted in an aqueous solution to obtain a precursor solution;

[0043] The precursor solution is dried to obtain a PEDOT-PSS composite sodium iron sulfate precursor;

[0044] The sodium iron sulfate precursor is heat-treated at 300-450° C. for 6-24 hours under an inert atmosphere to obtain a composite sodium iron sulfate positive electrode material.

[0045] EDOT is 3,4-ethylenedioxythiophene monomer, which polymerizes into PEDOT in the presence of an oxidant. Since PEDOT is insoluble in water, if PEDOT is directly mixed with sodium sulfate and ferrous sulfate, it cannot be fully dispersed evenly. After the final heat treatment, PEDOT can only be coated on the surface of sodium ferric sulfate, and the three-dimensional conductive network cannot be embedded in the interior of the sodium ferric sulfate particles. In this scheme, PSS (sodium polystyrene sulfonate) is introduced. PSS is grafted onto PEDOT to give it water solubility, so that PEDOT can be fully and evenly dispersed with sodium sulfate and ferrous sulfate in an aqueous solution, so that the particles of the composite sodium ferric sulfate positive electrode material obtained after the final heat treatment have a three-dimensional conductive network structure in which PEDOT is embedded in the interior of the sodium ferric sulfate particles, rather than just coating PEDOT on the surface of the sodium ferric sulfate particles. During the heat treatment, the ionic bonds between PEDOT and PSS are broken, and the partial or complete decomposition of PSS can further improve the conductivity of the polymer.

[0046] Therefore, the preparation method provided by the present invention can produce a composite sodium iron sulfate positive electrode material provided by an embodiment of the present invention, wherein the particles have a three-dimensional PEDOT conductive network embedded inside and the surface is coated with a PEDOT coating layer, and the material has better electrochemical properties.

[0047] The preparation method is specifically as follows:

[0048] S1. Mixed reaction

[0049] First, PSS, deionized water and EDOT were added into a reaction vessel and stirred thoroughly to disperse evenly;

[0050] Then, sodium sulfate, ferrous sulfate and an oxidant are added to the reaction solution, and the reaction is carried out under constant stirring until the solution turns dark blue or black, indicating that the reaction is complete.

[0051] Optionally, the oxidant includes at least one of ferric sulfate, sodium persulfate, ammonium persulfate, hydrogen peroxide and oxygen;

[0052] Preferably, the oxidant is ferric sulfate and sodium persulfate. The homogeneity of ferric sulfate and sodium persulfate with ferrous sulfate, a precursor of sodium ferric sulfate, allows the direct synthesis of the sodium ferric sulfate material composited with a conductive polymer by a one-pot method, reduces the purification steps, greatly reduces the complexity of the synthesis, and improves the atom economy and yield. More preferably, in order to keep the ferric sulfate dispersed more quickly and evenly, the ferric sulfate is added to the reaction vessel in the form of an aqueous solution.

[0053] Optionally, the molar ratio of sodium sulfate to ferrous sulfate is 1:1.5 to 2.5 (e.g., 1:1.5, 1:2 or 1:2.5);

[0054] Optionally, the feed mass ratio of PSS to EDOT is 10:1 to 5 (eg, 10:1, 10:2 or 10:5).

[0055] More specifically, in order to ensure that the prepared Duhe sodium ferric sulfate positive electrode material has better performance, the feed amounts are as follows: 31 to 314 parts of total PSS and EDOT, 1000 parts of sodium sulfate, and 1605 to 2675 parts of ferrous sulfate;

[0056] Optionally, the oxidant is 1 to 200 parts;

[0057] Optionally, the deionized water is 2500 to 100000 parts.

[0058] For example, the amount of materials added is: 31 parts of total PSS and EDOT, 1000 parts of sodium sulfate, 1605 parts of ferrous sulfate, 1 part of oxidant, and 2500 parts of deionized water;

[0059] Alternatively, the total amount of PSS and EDOT is 314 parts, sodium sulfate is 1000 parts, ferrous sulfate is 2675 parts, oxidant is 314 parts, and deionized water is 100000 parts;

[0060] Alternatively, the total amount of PSS and EDOT is 80 parts, sodium sulfate is 1000 parts, ferrous sulfate is 1800 parts, oxidant is 50 parts, and deionized water is 10000 parts;

[0061] Alternatively, the total amount of PSS and EDOT is 150 parts, sodium sulfate is 1000 parts, ferrous sulfate is 2000 parts, oxidant is 100 parts, and deionized water is 20000 parts;

[0062] Alternatively, the total amount of PSS and EDOT is 200 parts, sodium sulfate is 1000 parts, ferrous sulfate is 2200 parts, oxidant is 200 parts, and deionized water is 40000 parts;

[0063] Alternatively, the total amount of PSS and EDOT is 280 parts, sodium sulfate is 1000 parts, ferrous sulfate is 2400 parts, the oxidant is 270 parts, and deionized water is 80000 parts.

[0064] S2. Drying the precursor solution

[0065] After drying, a PEDOT-PSS composite sodium iron sulfate precursor is obtained.

[0066] Preferably, the drying method is spray drying. The reason for choosing spray drying is to obtain a sodium iron sulfate precursor with uniform particle size distribution and good morphology after spray drying.

[0067] S3. Heat treatment

[0068] The spray-dried sodium iron sulfate precursor is placed in an inert gas atmosphere and heat treated at a temperature of 300-450° C. (e.g., 300° C., 350° C., 400° C., or 450° C.) for 6-24 h (e.g., 6 h, 10 h, 15 h, 18 h, 20 h, or 24 h).

[0069] The heat treatment converts the sodium iron sulfate precursor into sodium iron sulfate, breaks the ionic bonds between PEDOT-PSS, and partially or completely decomposes PSS.

[0070] Optionally, the heat treatment process is performed under a nitrogen or argon atmosphere.

[0071] The positive electrode provided in the embodiment of the present invention is prepared by using the positive electrode material provided in the embodiment of the present invention, or the positive electrode material prepared by the preparation method provided in the embodiment of the present invention.

[0072] The sodium ion battery provided by the embodiment of the present invention includes the positive electrode provided by the embodiment of the present invention.

[0073] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0074] Examples 1-5

[0075] The embodiment provides a method for preparing a composite sodium iron sulfate positive electrode material, and the preparation process is as follows:

[0076] Add PSS, deionized water and EDOT into the container and stir to disperse evenly;

[0077] Add sodium sulfate, ferrous sulfate and a small amount of ferric sulfate aqueous solution into a reaction container, and stir the reaction until the solution turns dark blue to obtain a precursor solution;

[0078] The precursor solution is spray-dried to obtain a composite sodium iron sulfate precursor;

[0079] The precursor is heat-treated in a nitrogen atmosphere to obtain a PEDOT polymer-based composite sodium iron sulfate positive electrode material.

[0080] The specific parameter settings are shown in Table 1 below:

[0081] Table 1 Specific parameter settings of each embodiment

[0082]

[0083] Comparative Example 1

[0084] Compared with Example 1, in this comparative example, PSS was not added. After EDOT, sodium persulfate and ferric sulfate were added, the solution reacted rapidly and produced a large amount of precipitation, and a uniformly dispersed solution could not be formed for the next step of spray granulation experiment.

[0085] Comparative Example 2

[0086] Compared with Example 1, this comparative example did not add PSS, EDOT and oxidant.

[0087] Experimental Example 1

[0088] The SEM images of the composite sodium iron sulfate positive electrode material particles prepared in Example 1 and Comparative Example 2 are respectively Figure 1 and Figure 2 .from Figure 1 and Figure 2 It can be seen that the composite sodium ferric sulfate positive electrode material particles of Example 1 all have a three-dimensional conductive network embedded in the sodium ferric sulfate matrix and a coating layer structure on the surface; Comparative Example 2 has neither a surface coating layer structure nor an embedded conductive network structure, and is an ordinary sodium ferric sulfate positive electrode material.

[0089] Experimental Example 2

[0090] Conductivity test: Weigh 3g of compacted powder and put it into the mold cavity and vibrate to make the sample flat and uniform. Pressurize the mold to 30Mpa and use four probes to test the conductivity of the pressurized powder.

[0091] Sodium ion full battery performance test:

[0092] The AZO-doped sodium iron sulfate prepared in the above embodiment was used as the positive electrode material of the sodium ion battery, and was combined with a metal sodium sheet to form a CR2032 button cell. Among them, sodium iron sulfate, SP, and PVDF were homogenized in an NMP solution at a mass ratio of 9:0.5:0.5, and coated on an aluminum foil, and dried to form a positive electrode sheet. A fresh metal sodium sheet was used as the negative electrode of the battery, and a solution of 1.0 mol / L NaPF6 dissolved in PC:EMC:FEC=4:6:0.5 was used as the electrolyte. The button cell was assembled in an argon-filled glove box, and the capacity, rate, and cycle performance were tested.

[0093] Battery capacity test: Charge the installed battery to 4.3V at 0.1C, and then discharge it to 2.0V at 0.1C.

[0094] Battery rate performance test: Charge the assembled battery to 4.3V at 0.1C, and then discharge it to 2.0V at 2C.

[0095] Cycle life test: Charge the assembled battery to 4.3V at 1C, then discharge it to 2.0V at 1C, cycle 100 times, and record the capacity retention rate.

[0096] Table 2 Test results of various embodiments and comparative examples

[0097]

[0098]

[0099] It can be seen from Table 2 that the positive electrode materials prepared in each embodiment of the present invention have good electrochemical properties after being made into batteries, among which Examples 1-3 have better performance because the feeding range is within the preferred scheme of the present invention. The PSS and EDOT feeding amounts of Example 4 are small, and the conductivity, capacity and other properties of the prepared positive electrode material are worse than those of Examples 1-3, but the performance of the positive electrode material prepared without adding PSS and EDOT is still significantly better than that of the comparative example; the PSS and EDOT feeding amounts of Example 5 are large, and the conductivity, capacity and other properties of the prepared positive electrode material are worse than those of Examples 1-3, but the performance of the positive electrode material prepared without adding PSS and EDOT is still significantly better than that of the comparative example.

[0100] Comparing Comparative Example 1 with Example 1, since PSS was not added during the preparation process of Comparative Example 1, the polymer formed during the oxidative polymerization of EDOT was directly precipitated and could not be dissolved in the aqueous solution of ferrous sulfate and sodium sulfate, and a uniformly dispersed solution could not be prepared, so a uniformly mixed mixture of sodium ferrous sulfate precursor and PEDOT could not be formed by spray granulation. Comparative Example 2 was compared with Example 1, and no conductive polymer was added in Comparative Example 2, and the final material showed poor conductivity and battery performance.

[0101] In summary, in the composite sodium ferric sulfate positive electrode material provided by the embodiment of the present invention, the conductive network formed by PEDOT is embedded in the sodium ferric sulfate matrix and coated on the surface of the sodium ferric sulfate matrix, which can improve the conductivity, capacity and rate of the sodium ferric sulfate positive electrode material; and because PEDOT has good chemical stability, a coating layer is formed on the surface of sodium ferric sulfate, which can improve the interface stability of the sodium ferric sulfate positive electrode material.

[0102] In the preparation method provided in an embodiment of the present invention, PSS (sodium polystyrene sulfonate) is introduced during the preparation process, and ionic bonds are formed between PSS and PEDOT molecules, thereby improving the solubility of PEDOT in aqueous solution, so that PEDOT can be fully and evenly dispersed with sodium sulfate and ferrous sulfate in aqueous solution, thereby achieving a three-dimensional conductive network structure in which PEDOT is embedded in the sodium ferric sulfate particles in the particles of the composite sodium ferric sulfate positive electrode material obtained after the final heat treatment; and the sulfonate groups in the PSS are completely decomposed during the heat treatment process, resulting in the disappearance of the ionic bonds between PEDOT-PSS, which can also further improve the conductivity of the polymer.

[0103] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A composite sodium iron sulfate positive electrode material, characterized in that: The particles of the positive electrode material include a sodium ferric sulfate matrix, a three-dimensional conductive network embedded in the sodium ferric sulfate matrix, and a conductive coating layer coated outside the sodium ferric sulfate matrix; the three-dimensional conductive network and the conductive coating layer are both formed of PEDOT.

2. The positive electrode material according to claim 1, characterized in that The mass ratio of the sodium ferric sulfate matrix to PEDOT is 100:1-10.

3. A method for preparing the composite sodium iron sulfate positive electrode material according to claim 1 or 2, characterized in that: include: PSS, EDOT, sodium sulfate, ferrous sulfate and an oxidant as an initiator are mixed and reacted in an aqueous solution to obtain a precursor solution; Drying the precursor solution to obtain a PEDOT-PSS composite sodium iron sulfate precursor; The sodium iron sulfate precursor is heat-treated at 300-450° C. for 6-24 hours under an inert atmosphere to obtain the composite sodium iron sulfate positive electrode material.

4. The preparation method according to claim 3, characterized in that: The method of mixing PSS, EDOT, sodium sulfate, ferrous sulfate and an oxidant as an initiator to react includes: First, PSS, deionized water and EDOT were added into a reaction container and stirred and dispersed to obtain a reaction solution; Then, the sodium sulfate, the ferrous sulfate and the oxidant are added to the reaction solution, and the reaction is carried out under continuous stirring.

5. The preparation method according to claim 3, characterized in that: The oxidant includes at least one of ferric sulfate, sodium persulfate, ammonium persulfate, hydrogen peroxide and oxygen.

6. The preparation method according to claim 3, characterized in that: The oxidants are sodium persulfate and ferric sulfate.

7. The preparation method according to claim 4, characterized in that: The molar ratio of the sodium sulfate to the ferrous sulfate is 1:1.5-2.

5.

8. The preparation method according to claim 7, characterized in that: The feed mass ratio of the PSS to the EDOT is 10:1-5.

9. The preparation method according to claim 8, characterized in that: In terms of weight, the feed amounts are: 31-314 parts of the total amount of PSS and EDOT, 1000 parts of sodium sulfate, and 1605-2675 parts of ferrous sulfate.

10. The preparation method according to claim 9, characterized in that: The oxidant is 1 to 200 parts.

11. The preparation method according to claim 9, characterized in that: The deionized water is 2500-100000 parts.

12. The preparation method according to claim 3, characterized in that: The drying method is spray drying.

13. A positive electrode, characterized in that: The positive electrode material is prepared by the positive electrode material as described in claim 1 or 2 or the positive electrode material prepared by the preparation method as described in any one of claims 3 to 12.

14. A sodium ion battery, characterized in that: Comprising the positive electrode as claimed in claim 13.

Citation Information

Patent Citations

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN115064676A

Cited By

  • Composite sodium ferric sulfate positive electrode material and preparation method therefor, positive electrode, and sodium ion battery

    EP4510226A1